2006
DOI: 10.1128/jb.188.8.2745-2751.2006
|View full text |Cite
|
Sign up to set email alerts
|

Desulfovibrio gigas Flavodiiron Protein Affords Protection against Nitrosative Stress In Vivo

Abstract: Desulfovibrio gigas flavodiiron protein (FDP), rubredoxin:oxygen oxidoreductase (ROO), was proposed to be the terminal oxidase of a soluble electron transfer chain coupling NADH oxidation to oxygen reduction. However, several members from the FDP family, to which ROO belongs, revealed nitric oxide (NO) reductase activity. Therefore, the protection afforded by ROO against the cytotoxic effects of NO was here investigated. The NO and oxygen reductase activities of recombinant ROO in vitro were tested by amperome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
61
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 43 publications
9
61
0
Order By: Relevance
“…While the results here support the previously proposed idea of the role of ROO as a NO detoxifier (27,36), a more complex mechanism may explain the protection conferred by HCP. So far, HCPs have been described as having peroxidase activity (E. coli and D. desulfuricans ATCC 27774) (18) and hydroxylamine reductase activity (E. coli, Pyrococcus furiosus, and Rhodobacter capsulatus E1F1) (21)(22)(23).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…While the results here support the previously proposed idea of the role of ROO as a NO detoxifier (27,36), a more complex mechanism may explain the protection conferred by HCP. So far, HCPs have been described as having peroxidase activity (E. coli and D. desulfuricans ATCC 27774) (18) and hydroxylamine reductase activity (E. coli, Pyrococcus furiosus, and Rhodobacter capsulatus E1F1) (21)(22)(23).…”
Section: Discussionsupporting
confidence: 83%
“…In agreement, the D. gigas ROO was previously shown to be able to rescue an E. coli strain deleted in the NO-reductase flavodiiron gene and to have significant in vitro NO reductase activity (36).…”
Section: Discussionsupporting
confidence: 66%
“…In Desulfovibrio gigas, an equivalent enzyme complex was initially characterized as an oxidase, comprising the flavo-diiron protein (ROO, for rubredoxin oxygen oxido-reductase), a standalone rubredoxin and an NADH-rubredoxin oxidoreductase. The recombinant D. gigas ROO and reduced rubredoxin were found also to reduce NO to N 2 O, and physiological data suggested that the enzyme functions as an NO reductase in vivo [17]. Similarly, the D. vulgaris FprA functions as an NO reductase both in vitro and in vivo [18].…”
Section: Enzymes Of Nitrous Oxide Synthesis (A) Respiratory Nitric Oxmentioning
confidence: 99%
“…the FDPs from Moorella thermoacetica (8) and Desulfovibrio species (9,29)). The FDP from Escherichia coli, named flavorubredoxin (FlRd or NorV) (7,30), is selective toward NO (30,31).…”
mentioning
confidence: 99%